Comparative Transcriptome Analyses Reveal the Mechanisms Underlying Waterlogging Tolerance in Barley - Juan Zhu; Haoxin Yin; Cong Cao; Chengqun Sun; Mengna Zhang; Yi Hong; Yuhang Zhang; Chao Lv; Baojian Guo; Feifei Wang; Rugen Xu (Plants)
Waterlogging is becoming a global issue, affecting crop growth and yield in low-lying rainfed areas. A DH line, TamF169, showing superior waterlogging tolerance, and its waterlogging-sensitive parent, Franklin, were used to conduct transcriptome analyses. The results showed that 2209 and 2578 differentially expressed genes (DEGs) in Franklin and 1997 and 1709 DEGs in TamF169 were detected by comparing gene expression levels under control and waterlogging after 4 and 8 days, respectively, with 392 and 257 DEGs being specific to TamF169 after 4 and 8 days under waterlogging, respectively. KEGG analysis showed that glycolysis/gluconeogenesis, the MAPK signaling pathway, plant hormone signaling, and galactose metabolism pathways were significantly enriched in the waterlogging-tolerant genotype TamF169 four days after waterlogging. The qPCR results were consistent with the transcriptome data, suggesting the reliability of the transcriptome sequencing. A total of 13 genes in the mapping region of a QTL for root cortical aerenchyma (RCA) showed different expression levels in Franklin or TamF169, and the potential candidate genes for RCA−QTL are discussed. This study offers valuable information on the mechanism of tolerance to waterlogging stress in the DH line TamF169 and provides the candidate genes for RCA−QTL.